2015
DOI: 10.1111/1440-1681.12472
|View full text |Cite
|
Sign up to set email alerts
|

Asiatic acid alleviates cardiovascular remodelling in rats with L‐NAME‐induced hypertension

Abstract: A previous study demonstrated the antihypertensive effect of asiatic acid. The current study investigates the effect of asiatic acid on cardiovascular remodelling and possible mechanisms involved in Nω -nitro-L-arginine methyl ester hydrochloride (L-NAME)-induced hypertensive rats. Male Sprague-Dawley rats were treated with L-NAME (40 mg/kg per day) for 3 weeks in order to induce hypertension. Hypertensive rats were administered asiatic acid (20 mg/kg per day) or vehicle for a further 2 weeks. It was found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 47 publications
6
47
0
Order By: Relevance
“…Glycyrrhizin, the similar pentacyclic triterpene compound, has attenuated pulmonary vascular remodeling, as is reported17. Asiatic acid can alleviate cardiovascular remodeling due to its antioxidant effect18, and inhibit cardiac hypertrophy by blocking TGF-β1 pathway19. AKBA has similar structure and activity with Asiatic acid20.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Glycyrrhizin, the similar pentacyclic triterpene compound, has attenuated pulmonary vascular remodeling, as is reported17. Asiatic acid can alleviate cardiovascular remodeling due to its antioxidant effect18, and inhibit cardiac hypertrophy by blocking TGF-β1 pathway19. AKBA has similar structure and activity with Asiatic acid20.…”
mentioning
confidence: 76%
“…In another word, drugs inhibiting TGF-β1 pathway or in combination with antioxidant effect may have potential vasoprotection in vascular remodeling. Pentacyclic triterpene compounds structurally similar to AKBA, such as glycyrrhizin and Asiatic acid, have been reported therapeutic effects on cardiovascular remodeling and fibrosis171819. Accordingly, AKBA may also have potential implication in treating vascular remodeling of hypertension, without proper mechanisms, however.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is closely interwoven with vascular inflammation as excessive ROS production creates a pro-inflammatory state and enhances the expression of inflammatory cytokines. 23 Our work showed that aortic IFN-γ and VCAM-1 mRNA were significantly higher in hypertensive rats compared to expression in both the control and H 2 S control groups. Robles-Vera et al 24 found that rats who received l-NAME had higher mRNA levels of IFN-γ, which is Concurrent administration of H 2 S and l-NAME ameliorated the increase in aortic IFN-γ and VCAM-1 mRNA, which is consistent with the observations of Pan et al, 26 who reported that NaHS suppressed (in a concentration-dependent manner) TNF-α-induced expression of ICAM, VCAM-1, E-selectin, and monocyte adhesion in human umbilical vein endothelial cells.…”
Section: Discussionmentioning
confidence: 52%
“…Oxidative stress is closely interwoven with vascular inflammation as excessive ROS production creates a pro‐inflammatory state and enhances the expression of inflammatory cytokines . Our work showed that aortic IFN‐γ and VCAM‐1 mRNA were significantly higher in hypertensive rats compared to expression in both the control and H 2 S control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation